2014
DOI: 10.1590/s0102-86502014000200004
|View full text |Cite
|
Sign up to set email alerts
|

The ileum positively regulates hepatic regeneration in rats

Abstract: PURPOSE:To test the hypothesis that liver regeneration after partial hepatectomy can be influenced by the ileum. METHODS:Eighteen Wistar rats were distributed into groups of six animals: 1 -ileum resection+ hepatectomy 2/3; 2 -hepatectomy 2/3, and 3 -sham. Anesthesia with ketamine and xylazine i.p., aseptic technique, analgesia with meperidine (10mg/kg s.c.). On day 6, serum ALT, AST, alkaline phosphatase (AP) and albumin were measured. Liver regeneration and hepatocyte mitosis were quantified.Statistical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Surgical and genetic disruptions of normal BA enterohepatic circulation and influx into the liver severely attenuated liver regeneration after PHx in mice [60]. PHx accompanied by ileal resection resulted in diminished liver regeneration capability, most likely due to loss of BA reabsorption in the ileum [61]. These findings highlight BA circulation through the gut-liver axis as an important regulatory component of the liver regeneration program.…”
Section: The Effects Of Bile Acids On Liver Regenerationmentioning
confidence: 99%
“…Surgical and genetic disruptions of normal BA enterohepatic circulation and influx into the liver severely attenuated liver regeneration after PHx in mice [60]. PHx accompanied by ileal resection resulted in diminished liver regeneration capability, most likely due to loss of BA reabsorption in the ileum [61]. These findings highlight BA circulation through the gut-liver axis as an important regulatory component of the liver regeneration program.…”
Section: The Effects Of Bile Acids On Liver Regenerationmentioning
confidence: 99%
“…A number of previous studies have shown that lack or disruption of BA influx into the liver markedly inhibits or delays the regenerative process, whereas excessive BAs could be cytotoxic, and in turn might also slow LR. [13][14][15][16] Despite these findings, the scarcity of comprehensive metabolomics and metagenomics fingerprinting has hampered a complete understanding of the interplay between IB and the host response during LR. As previously shown, not all genera of bacteria are responsible for LR, such as Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we demonstrated that the ileus acts positively on the parameters of hepatic regeneration in rats 15 .…”
Section: Discussionmentioning
confidence: 82%
“…It is known that ileus is essential to the process of liver regeneration 15 . A study in rats submitted to hepatectomy and simultaneous resection of a segment of only 1cm of the colon concluded that there was a higher degree of liver regeneration than in the animals submitted to isolated hepatectomy 16 .…”
Section: Discussionmentioning
confidence: 99%